The Factors that Effect to Take Part in Betting - Alp Çelik (ümit doğan üstün, 2016)
Because of its' nature, betting in sports includes factors such as huge revenue, hot money flow, entertainment, thrill, dreams and happening of these dreams. Herewith, these factors pointed out in society effects people's betting motivation. The purpose of this study was to investigate the factors that effects participators/players to take part in betting. While the universe of the study composed players in Ankara, the sampling group consisted of a legal bookmaker of Spor Toto Teşkilat Bakanlığı and Türkiye Jokey Kulübü that is easily accessible and has a huge rate of revenue. In total, 80 participators (15 students, 20 workers, 20 civil servants, 15 handicraftsmen and 10 self employments) participated to study and filled in the questionnaire that expert opinion was taken, validity and reliability were done, According to the results acquired, it was determined that participators take part in betting to enhance the quality of life, bring enjoy and attraction of their life, getting rid of stress and most importantly making money because of some reasons such as economic crisis and financial difficulty in their society, their low income level and their debts.